Perspectives on sustainability integration in the organization's DNA - Khalili, Amjad; Ismail, Md Yusof; Karim, A.N. Mustafizul (Noor Publishing, 2017)
This book is a useful reference for scholars and managers interested to understand the sustainability issues that enterprises are trying to achieve. Simply it introduces the concept of sustainability, the different models adopted by organizations worldwide, the elements that characterize sustainability paradigm. Additionally, it handles the linkages with key Operations Management practices including the ISO standards represented by Quality Management System, Environmental Management System, and the two philosophies namely Total Quality Management and Lean Manufacturing. Views and criticisms aligned with numerous researchers for these numerous practices are discussed in this book. Furthermore, how sustainability of enterprises are linked to their DNA structure is presented. It is the common goal that manufacturers and managers in service businesses are challenging to achieve in this competitive world